Fear of Needles and Seasonal Influenza Vaccine Acceptance Amongst Adults in the United Arab Emirates: A Cross-Sectional Study and Implications for Nursing - Gabriel Andrade PhD; Khadiga Yasser Abdelraouf Abdelmonem MBBS; Nour Alqaderi MBBS; Hajar Jamal Teir MBBS; Ahmed Banibella Abdelmagied Elamin MBBS; Dalia Bedewy PhD (SAGE Publishing, 2024)
Introduction Seasonal influenza remains a challenge in the United Arab Emirates, and vaccination is an important preventive measure. However, fear of needles may be an obstacle in vaccination efforts. Objective The purpose of this study was to determine, in a non-clinical sample obtained from the UAE, how much of an impact fear of needles has on the decision to receive the seasonal influenza vaccine. Methods In the period September-December 2022, 372 participants were surveyed on their willingness to be vaccinated, their level of vaccine knowledge, and their level of fear of needles. Logistic regression models were used to assess the impact of fear of needles and vaccine knowledge on the decision to accept the seasonal influenza vaccine. Results Fear of needles and vaccine knowledge are significant predictors in the decision to receive the vaccine. There were no gender or ethnic differences in fear of needles, but there were differences in the decision to receive the vaccines, with women and non-Arabs being more hesitant. Conclusion Fear of needles may be an important variable to account for in public policies designed to improve vaccination rates in the UAE. For public health policy in the UAE, this implies that authorities must dedicate efforts to manage fear of needles in the general population. Efforts to address fear of vaccines in the general population must be made with proper training of nurses. Alternatively, authorities may need to seek oral alternatives for the administration of the seasonal influenza vaccine.